2000
DOI: 10.1002/(sici)1097-0282(200003)53:3<233::aid-bip3>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a strong sulfur-aromatic interaction derived from crystallographic data

Abstract: We have uncovered new evidence for a significant interaction between divalent sulfur atoms and aromatic rings. Our study involves a statistical analysis of interatomic distances and other geometric descriptors derived from entries in the Cambridge Crystallographic Database (F. H. Allen and O. Kennard, Chem. Design Auto. News, 1993, Vol. 8, pp. 1 and 31–37). A set of descriptors was defined sufficient in number and type so as to elucidate completely the preferred geometry of interaction between six‐membered aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…For example, an interaction between sulfur and the face of the phenylalanine benzene ring has been reported to be favored in some studies (59) and unfavored in others (35,37). Tauer et al (59) modeled interactions of H 2 S with benzene and reported that the optimal intermonomer distance was 3.8 Å with an interaction energy of -2.81 kcal mol −1 .…”
Section: Enzyme-inhibitor Sulfur-aromatic Interactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, an interaction between sulfur and the face of the phenylalanine benzene ring has been reported to be favored in some studies (59) and unfavored in others (35,37). Tauer et al (59) modeled interactions of H 2 S with benzene and reported that the optimal intermonomer distance was 3.8 Å with an interaction energy of -2.81 kcal mol −1 .…”
Section: Enzyme-inhibitor Sulfur-aromatic Interactionsmentioning
confidence: 99%
“…However, given that sulfur has a low electronegativity (essentially the same as carbon, 2.58); it is difficult to imagine this scenario accounting for all of the observed favorable effects. It is possible that the sulfur lone pairs could interact favorably with the ring hydrogens (35). However this interaction would depend greatly upon the geometry of the bound inhibitor.…”
Section: Enzyme-inhibitor Sulfur-aromatic Interactionsmentioning
confidence: 99%
See 3 more Smart Citations